2021
DOI: 10.1111/acer.14724
|View full text |Cite
|
Sign up to set email alerts
|

Is talk cheap? Correspondence between self‐attributions about changes in drinking and longitudinal changes in drinking during the 2019 coronavirus pandemic

Abstract: Background There are concerns that the coronavirus disease 2019 (COVID‐19) pandemic may increase drinking, but most accounts to date are cross‐sectional studies of self‐attributions about alcohol‐related impacts and the accuracy of those perceptions has not been investigated. The current study examined the correspondence between self‐attributions of pandemic‐related changes in drinking and longitudinally‐measured changes in drinking and alcohol‐related consequences in a sample of emerging adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 32 publications
0
15
2
Order By: Relevance
“…However, our results found that there was no difference between cross-sectional and longitudinal studies in the size of effect, and that study quality did not moderate effect size. Further, recent research has demonstrated robust correspondence between subjective self-report measures and longitudinal quantitative self-report methods (Minhas et al, 2021). These points assuage concerns regarding our reliance on longitudinal data.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results found that there was no difference between cross-sectional and longitudinal studies in the size of effect, and that study quality did not moderate effect size. Further, recent research has demonstrated robust correspondence between subjective self-report measures and longitudinal quantitative self-report methods (Minhas et al, 2021). These points assuage concerns regarding our reliance on longitudinal data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a follow-up survey with the same sample confirmed sustained increases in consumption [13][14][15], and the other three longitudinal studies conducted in the United States so far [11,12,70], despite not providing detailed information on drinking patterns, also found increases in alcohol consumption during the COVID-19 pandemic. Furthermore, the meta-analysis by Acuff et al (2002) found no difference between cross-sectional and longitudinal studies in the size of the effect, and recent research in Canada revealed longitudinal patterns of drinking that were substantively consistent with self-attributions [71]. A fourth limitation is that our estimates of alcohol consumption may underestimate total consumption, which is a well-known limitation of collecting self-reported data on substance use using surveys [72,73]; however, this approach is still considered reliable for measuring alcohol consumption [74].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the meta‐analysis by Acuff et al . (2002) found no difference between cross‐sectional and longitudinal studies in the size of the effect, and recent research in Canada revealed longitudinal patterns of drinking that were substantively consistent with self‐attributions [ 71 ]. A fourth limitation is that our estimates of alcohol consumption may underestimate total consumption, which is a well‐known limitation of collecting self‐reported data on substance use using surveys [ 72 , 73 ]; however, this approach is still considered reliable for measuring alcohol consumption [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Killgore et al found an increase in mean AUDIT scores during a lockdown period in a sample recruited from the Amazon Mechanical Turn (MTurk) online crowdsourcing platform [ 36 ]. Further, recent research has demonstrated robust correspondence between subjective self-report measures and longitudinal quantitative self-report methods [ 37 ]. The participants who had responded may not be representative of the users of the psychoACTIF Website.…”
Section: Discussionmentioning
confidence: 99%